Experimental Evaluation of Innovated Mixed Flow Wind Turbine for Updraft Solar Power Generation Systems - ., Koh Kelly (IRC, 2016)
Solar updraft power systems (SUPS) utilize solar energy to produce electrical energy. In a typical solar updraft power system, the air flow enters the collector radially and exit through the chimney axially. However, the existing wind turbine operates at such that the air enters and exits in the same direction either axial-axial or radialradial. The main objective of this study is to determine the characteristic of wind turbine through experimental investigation for four different cases; two small and two big wind turbines with blades placed with an orientation of 45 degrees and 70 degrees. The scopes of this study include fabrication of four new units of designed wind turbines, experimental setup and carrying out experimental measurements to determinate wind velocity approaching the turbine, rotational speed of turbine, and electrical output power. The experimental evaluation was conducted four times for each case to obtain average value with the same experimental setup. From the experimental data collected, the characteristic curve of each of the case has been established in terms of power coefficient and tip speed ratio.